Trade Liberalization, Economic Reforms and Foreign Direct Investment – A Critical Analysis of the Political Transformation in Vietnam - Van Chien Nguyen (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to discuss the trends of integration into the global economy since political and economic reforms (so-called Doimoi) and its influence on every presence of foreign investment in Vietnam. Lasting 20-year-war period and ended in 1975, by the mid-1980s per capita income was stuck between 200 and 300, Vietnam’s government introduced Doimoi through a series of reforms, and steered the country to be a socialist-oriented market economy. Based on the analysis of reform process and integration, the results are concerned. Our results demonstrate that foreign direct investment performance has significantly embraced trade liberalization with gusto. Further, the open trade policy in relation to FTAs could significantly promote foreign investment and maximize its benefits on the economy.